2012
DOI: 10.1901/jaba.2012.45-281
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Teaching Interaction Procedure to Social Stories for People With Autism

Abstract: This study compared social stories and the teaching interaction procedure to teach social skills to 6 children and adolescents with an autism spectrum disorder. Researchers taught 18 social skills with social stories and 18 social skills with the teaching interaction procedure within a parallel treatment design. The teaching interaction procedure resulted in mastery of all 18 skills across the 6 participants. Social stories, in the same amount of teaching sessions, resulted in mastery of 4 of the 18 social ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1
14

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 24 publications
4
64
1
14
Order By: Relevance
“…Ty was currently not attending school and was receiving all behavioural intervention services in a community-based clinic. Ty's clinical intervention included one-to-one discrete trial teaching and group discrete trial teaching, both which utilised a flexible prompt fading approach (e.g., Leaf et al, 2013a).Additionally, Ty's clinical intervention included attending a social skills group where the cool versus not cool procedure (e.g., Leaf et al, 2012a) and the teaching interaction procedure (e.g., Leaf et al, 2012b) were the primary teaching methodologies utilised. The focus of these interventions was to increase Ty's general knowledge, language and social behaviours.…”
Section: Participantsmentioning
confidence: 99%
“…Ty was currently not attending school and was receiving all behavioural intervention services in a community-based clinic. Ty's clinical intervention included one-to-one discrete trial teaching and group discrete trial teaching, both which utilised a flexible prompt fading approach (e.g., Leaf et al, 2013a).Additionally, Ty's clinical intervention included attending a social skills group where the cool versus not cool procedure (e.g., Leaf et al, 2012a) and the teaching interaction procedure (e.g., Leaf et al, 2012b) were the primary teaching methodologies utilised. The focus of these interventions was to increase Ty's general knowledge, language and social behaviours.…”
Section: Participantsmentioning
confidence: 99%
“…This conversation arrangement required individuals to discriminate when to engage in each skill (e.g., continuing to discuss a topic of conversation when the listener is interested and changing the topic of conversation when the listener is uninterested), thereby simulating a typical conversation. This arrangement is in contrast to teaching each skill in different sessions during brief interactions (e.g., two to three reciprocal exchanges) between the individual and the conversation partner (Dotson, Leaf, Sheldon, & Sherman, 2010;Leaf et al, 2012;Leaf et al, 2009). For example, Dotson et al (2010) programmed three-turn conversation sessions in which the child had one opportunity to engage in the corresponding skill.…”
mentioning
confidence: 99%
“…Studies have demonstrated the effectiveness of BST for teaching skills to individuals with ASD (e.g., Leaf et al, 2012;Palmen et al, 2012) and for teaching job-related skills to individuals with other disabilities (Gear, Bobzien, Judge, & Raver, 2011;Whang, Fawcett, & Mathews, 1984). Our preliminary clinical work further suggests that stimulus prompts (e.g., text prompts) may help promote generalization of the skills from the training location to the job site.…”
Section: Discussionmentioning
confidence: 56%